LANDSCAPE CHANGE WITH THE TRANSPOSITION OF THE SÃO FRANCISCO RIVER, IN THE DOMAIN CAATINGA, PERNAMBUCO - de Moura Melo, Lorena; de Lima Pessoa, Mayara Maria; Araújo Silva, Emanuel; de Carvalho Chaves, Lúcia de Fatima (Floresta, 2021)
Landscape change with the transposition of the São Francisco River, in the Domain Caatinga, Pernambuco.The objective of this study was to evaluate the dynamics of land use and cover and the landscape structure, as well as the landscape structure, of the Directly Affected Area by Integration Project of the São Francisco River with the Northeastern Hydrographic Basins, from the East Axis portion located in the State of Pernambuco, Brazil. For this purpose, TM / Landsat 5 and OLI / Landsat 8 images were used, referring to the years 1998, 2008 and 2018, periods before, during and after the transposition, respectively. The land use and land cover classes used in this analysis were savanna-steppe, savanna-steppe, anthropized and / or uncovered area, water resources and agricultural area. Image processing and classification were performed using the QGIS software. Also, studies related to the landscape structure were carried out, using different types of metrics, processed in the Patch Analyst tool, an extension of ArcGIS 10.5. As a result of the analysis of the 20 years, it was obtained that the savanna-steppe vegetation cover showed a 13.86% reduction. However, there were additions in the areas of ciliary savanna, water resources, agricultural area and anthropized area in 1.93%, 0.11%, 0.31% and 11.51%, respectively. Furthermore, there was an increase in forest fragmentation, which corroborated with the results regarding for the core area metrics, which show that there has been a reduction in the size of the fragments and a trend towards the loss of the core areas, due to the edge effect.